2020
DOI: 10.1016/j.drugalcdep.2019.107811
|View full text |Cite
|
Sign up to set email alerts
|

Acute alcohol intake alters resting state functional connectivity of nucleus accumbens with pain-related corticolimbic structures

Abstract: Background-The nucleus accumbens (NAc) is a ventral striatal structure underlying reward, reinforcement, and motivation, with extensive anatomic and functional connections to a wide range of affective processing structures (medial prefrontal cortex (mPFC), amygdala, and insula). Characterizing how acute alcohol intake affects resting state functional connectivity (rsFC) between the nucleus accumbens (NAc) and these regions will improve mechanistic understanding of alcohol's neurobehavioral effects, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…While previous studies have examined the effects of acute alcohol on rsFC (Boissoneault et al, 2020;Gorka et al, 2018), this work provides novel information indicating that acute alcohol decreases VTA-caudate rsFC. Although the VTA has greater structural connectivity to the nucleus accumbens (Haber & Knutson, 2010), prior studies have demonstrated VTA-caudate connectivity at rest (Murty et al, 2014;Tomasi & Volkow, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…While previous studies have examined the effects of acute alcohol on rsFC (Boissoneault et al, 2020;Gorka et al, 2018), this work provides novel information indicating that acute alcohol decreases VTA-caudate rsFC. Although the VTA has greater structural connectivity to the nucleus accumbens (Haber & Knutson, 2010), prior studies have demonstrated VTA-caudate connectivity at rest (Murty et al, 2014;Tomasi & Volkow, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…between these areas at rest following acute alcohol administration (Boissoneault et al, 2020; but see Han et al, 2021) and in abstinent heavy drinkers during a monetary reward task (Forbes et al, 2014).…”
Section: Discussion Overviewmentioning
confidence: 99%
“…In healthy adults, a pain modulation training protocol that reduced experimental pain sensitivity also reduced resting connectivity between these structures (Sevel et al, 2020). At the same time, alterations in connectivity have been detected between these areas at rest following acute alcohol administration (Boissoneault et al, 2020; but see Han et al, 2021) and in abstinent heavy drinkers during a monetary reward task (Forbes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The right and left nucleus accumbens (NAcc) are subcortical brain structures, located within the ventral striatum, that serve as a key limbic-motor interface, and have an important role in Pavlovian learning [1,2]. This means that the right and left NAcc contribute to the regulation of emotional and motivation processing [3], incentive salience [4], pleasure, reward, and reinforcement [5]. In addition, neural reactivity to food-and/or drug-related reward cues evokes robust dopamine responses in the right and left NAcc [1].…”
Section: Introductionmentioning
confidence: 99%